Morphological and molecular evidence for a new species from China: Piper semi-transparens (Piperaceae) - Hao, Chao-Yun; Wu, Bao-Duo; Qin, Xiao-Wei; Wu, Gang; Deng, Hai-Yan; Tan, Yun-Hong (Phytotaxa, 2020)
We conducted morphological and molecular analyses to describe a new species of Piperaceae, Piper semi-transparens, which was observed in Hainan, Guangdong and Guangxi Provinces, China. Detailed morphological comparisons between the newly discovered species and other members of Piper indicate that Piper semi-transparens is similar to P. bonii and P. bonii var. macrophyllum, from which it differs in having glabrous leaf blades; stem densely short and unbranched pubescent when young, glabrous when mature; veins 5(–7); stamens 2; stigmas 3, rarely 4; spikes color white when mature; floral bracts glabrous; pericarp white and semi-transparent. Molecular analyses based on the ITS marker of nuclear ribosomal DNA strongly support that P. semi-transparens is a new species in the genus Piper, most closely related to P. bonii and P. bonii var. macrophyllum.